Exome capture from the spruce and pine giga‐genomes. (5th August 2016) - Suren, H.; Hodgins, K. A.; Yeaman, S.; Nurkowski, K. A.; Smets, P.; Rieseberg, L. H.; Aitken, S. N.; Holliday, J. A.
Abstract: Sequence capture is a flexible tool for generating reduced representation libraries, particularly in species with massive genomes. We used an exome capture approach to sequence the gene space of two of the dominant species in Canadian boreal and montane forests – interior spruce ( Picea glauca x engelmanii ) and lodgepole pine ( Pinus contorta ). Transcriptome data generated with RNA‐seq were coupled with draft genome sequences to design baits corresponding to 26 824 genes from pine and 28 649 genes from spruce. A total of 579 samples for spruce and 631 samples for pine were included, as well as two pine congeners and six spruce congeners. More than 50% of targeted regions were sequenced at >10× depth in each species, while 12% captured near‐target regions within 500 bp of a bait position were sequenced to a depth >10×. Much of our read data arose from off‐target regions, which was likely due to the fragmented and incomplete nature of the draft genome assemblies. Capture in general was successful for the related species, suggesting that baits designed for a single species are likely to successfully capture sequences from congeners. From these data, we called approximately 10 million SNPs and INDELs in each species from coding regions, introns, untranslated and flanking regions, as well as from the intergenic space. Our study demonstrates the utility of sequence capture for resequencing in complex conifer genomes, suggests guidelines for improving capture efficiency and provides a rich resource of genetic variants for studies of selection and local adaptation in these species.